Biogas Generation from Domestic Solid Wastes in Mesophilic Anaerobic Digestion - Usman M. A.; Olanipekun O. O.; Kareem O. M. (International Journal of Research in Chemistry and Environment (IJRCE), 2011)
Biogas was generated from domestic solid wastes collected from residential area in the University of Lagos in a mesophilic laboratory-scale batch digester by anaerobic digestion over a retention time of 20 days at 400C. The wastes collected were characterized and organic wastes are used as feedstock in the setups. Two setups were adopted in the investigation namely digesters A and B. In digester A, 300g of the wastes was mixed water and in the digester B the wastes was blended with poultry dropping in ratio 2:1 and mixed with water, to form slurry in both cases. The volume of produced was monitored every day and 10ml of digestates were withdrawn at interval of four days for analysis to estimate the Total Solids(TS), Total Suspended Solids(TSS) and Total Volatile Solids(TVS). The average volumes of biogas generated in the setups were 40 and 44.45 ml day-1 respectively. This corresponded to 60 and 45 ml biogas (g l-1VS) in the respective digesters over the retention time. Also, the average values of TS, TSS and TVS obtained during the digestion period were 70,167, 52833 and 14667 mg l-1 respectively for the digester A and 73500, 53833 and 10833 mg l-1 respectively for digester B. It was thus inferred that domestic solid wastes can be collected, and treated in a non-polluting, environmentally feasible cost effective process to produced biogas.